Peran Media Sosial dalam Mewujudkan Gerakan Hijrah: Studi terhadap Whatsapp Grup AMSHAH (Amani Shalihatunnisa) - Eka Septa Dini; Siti Mariyam (Institut Agama Islam Negeri Kendari, 2022)
Social media is an online media that can make it easier for users to communicate and share information without time limits. One of the social media that is widely used by the community is the WhatsApp application. Whatsapp is an internet-based application that allows its users to communicate with its supporting features. This study aims to: (1) determine the role of social media whatsapp for the AMSHAH community, and (2) find out the concept of hijrah changes that occur in the AMSHAH community. This study uses a qualitative descriptive method to provide facts about the role of social media whatsapp for the AMSHAH community. The results showed that the role of social media whatsapp for AMSHAH there were 5, namely as social interaction, as entertainment, as information, creativity, and as a medium of da'wah. Meanwhile, the concept of changing hijrah in the AMSHAH community has 3, namely: First, physical changes, members have started to use syar'i clothes for their daily lives. Second, a change of mind. members who at first only thought about the world and then after gaining knowledge about religion, they changed their minds by always relating it to the hereafter. Third, namely behavioral changes, members have started to leave negative activities and turn them into positive activities.Keywords: Amani Salihatunnisa; Migrate; The Role of Social Media